Living Qur'an dalam Tradisi Yasinan, Tahlilan, dan Khataman: Dialektika Al-Qur'an, Budaya Lokal, dan Identitas Keislaman - Abdul Salam; Nailil Murod, Miftahun; Muslim (Dirosah Islamiyah, 2026)
This study examines the traditions of Yasinan, Tahlilan, and Khataman as manifestations of the Living Qur'an, highlighting the dynamic relationship between the Qur'an, local culture, and Islamic identity. The research addresses three main questions: how these traditions represent the community's reception of the Qur'an, how the interaction between Qur'anic values and local cultural practices is constructed, and how these traditions contribute to the formation of Islamic identity. The study aims to analyze Yasinan, Tahlilan, and Khataman as expressions of the Living Qur'an while explaining the dynamic relationship between the Qur'anic text, local traditions, and the social life of Muslim communities. This research employs a qualitative method based on library research using the Living Qur'an perspective. The data were collected from the Qur'an, hadith, classical and contemporary Qur'anic commentaries, scholarly books, and relevant academic journal articles, and were analyzed through descriptive-analytical content analysis. The findings reveal that the traditions of Yasinan, Tahlilan, and Khataman are not merely religious rituals but also represent the community's reception and actualization of Qur'anic values in everyday life. These traditions create a dynamic interaction between normative Islamic teachings and local cultural expressions, fostering an adaptive and moderate Islamic identity while strengthening social solidarity without compromising the essential values of the Qur'an